2016
DOI: 10.1590/18069657rbcs20150036
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and Classification of Soils Containing Carbonate on the Apodi Plateau, Brazil

Abstract: ABSTRACT:Information is scarce on the genesis and classification of soils derived from calcareous rocks in the Northeastern region of Brazil. This study describes the morphological, physical, chemical, mineralogical, and micromorphological properties of four soil profiles (P1-P4) located in the Apodi Plateau. A pedogenesis hypothesis and soil classification, according to the Brazilian System of Soil Classification (SiBCS), are proposed for these profiles. The interactions between parent material, surface topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…There are closed basin or dry valleys in various sizes and shapes, poor drainage, and hilly up to ramps landform. The soil classification in Karst are Entisol, Mollisol, Alfisol, Vertisol, Inceptisol [17][18][19][20]. Karst soils are taken from five locations (Gunungkidul, Wonogiri, Grobogan, Buayan Kebumen, and Padalarang Bandung) around the limestone hills with varies pH from slightly acid to alkaline.…”
Section: Resultsmentioning
confidence: 99%
“…There are closed basin or dry valleys in various sizes and shapes, poor drainage, and hilly up to ramps landform. The soil classification in Karst are Entisol, Mollisol, Alfisol, Vertisol, Inceptisol [17][18][19][20]. Karst soils are taken from five locations (Gunungkidul, Wonogiri, Grobogan, Buayan Kebumen, and Padalarang Bandung) around the limestone hills with varies pH from slightly acid to alkaline.…”
Section: Resultsmentioning
confidence: 99%
“…Mansehra was decalcified deeper compared to other soils due to effective rainfall as this series occur on wide very gently sloping sites in loess plain in a subhumid climate. Ferreira et al (2016) reported that CaCO 3 content increased with soil depth. The Mansehra soil had greater OM compared to other soils, probably due to greater clay content and cooler climate.…”
Section: Density Fractionationmentioning
confidence: 99%
“…Sua distribuição é irregular em alguns perfi s no compartimento dfv, como em P4, P8, P9 e P10. Esses dois elementos garantem valores muito altos de saturação por bases (> 90%), atribuindo aos solos generalizadamente um caráter hipereutrófi co, condizente com outros estudos realizados por Oliveira et al (1998); Naime et al (2007); Ferreira et al (2016); Oliveira et al (2018), entre outros, em solos do semiárido.…”
Section: Propriedades Químicas Dos Solosunclassified